Cheap and sensitive polymer/bismuth film modified electrode for simultaneous determination of Pb(II) and Cd(II) ions. Issue 10 (October 2021) - Yifru, Alemayehu; Dare, Gossa; Demissie, Taye B.; Mehretie, Solomon; Admassie, Shimelis
Abstract: Different aminonaphetalenesulphonic acid derivatives like 5-aminonaphthalene-1-sulphonic acid (5AN1SA), 2-aminonaphthalene-1-sulphonic acid (2AN1SA), 8-aminonaphthalene-2-sulphonic acid (8AN2SA) and 4-amino-3-hydroxynaphthalene-1-sulphonic acid (4A3HN1SA) were used to construct polymer/bismuth film modified electrode for simultaneous determination of Pb(II) and Cd(II) ions with the aim of developing a cheaper and sensitive electrode that could possibly replace Nafion. Among the different modified electrodes, poly (8AN2SA)/bismuth film modified electrodes showed the highest electrochemical response for both ions. These electrochemical results were also supported by density functional theory (DFT) calculations. Based on these experimental and theoretical results, poly (8AN2SA)/bismuth film glassy carbon modified electrode was further investigated to develop a simple and sensitive electrochemical method for the simultaneous determination of Pb(II) and Cd(II) ions. After optimizing the different experimental parameters, the proposed method gave a linear range of 1–40 μg/L with the detection limit of 0.38 and 0.08 μg/L for the simultaneous determination of Pb(II) and Cd(II) ions, respectively. Abstract : 8-Aminonaphthalene-2-sulphonic acid, Square wave anodic stripping voltammetry, Pb(II), Cd(II).